2008
DOI: 10.1088/0004-6256/136/3/1325
|View full text |Cite
|
Sign up to set email alerts
|

The Alhambra Survey: A Large Area Multimedium-Band Optical and Near-Infrared Photometric Survey

Abstract: Here we describe the first results of the ALHAMBRA survey which provides cosmic tomography of the evolution of the contents of the Universe over most of Cosmic history. Our novel approach employs 20 contiguous, equal-width, medium-band filters covering from 3500Å to 9700Å, plus the standard JHK s near-infrared bands, to observe a total area of 4 square degrees on the sky. The -2optical photometric system has been designed to maximize the number of objects with accurate classification by Spectral Energy Distrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
187
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 154 publications
(190 citation statements)
references
References 64 publications
2
187
0
1
Order By: Relevance
“…The Advanced Large, Homogeneous Area Medium Band Redshift Astronomical (ALHAMBRA 1 , Moles et al 2008) survey is a 20 narrow-band optical and three broad-band NIR (JHK) photometric survey imaged with the wide-field cameras LAICA and OMEGA-2000 respectively, at the Calar Alto Observatory (Spain) 2 .…”
Section: The Alhambra Surveymentioning
confidence: 99%
“…The Advanced Large, Homogeneous Area Medium Band Redshift Astronomical (ALHAMBRA 1 , Moles et al 2008) survey is a 20 narrow-band optical and three broad-band NIR (JHK) photometric survey imaged with the wide-field cameras LAICA and OMEGA-2000 respectively, at the Calar Alto Observatory (Spain) 2 .…”
Section: The Alhambra Surveymentioning
confidence: 99%
“…The ALHAMBRA survey provides a photometric data set over 20 contiguous, equal-width (∼300 Å), non-overlapping, medium-band optical filters (3500 Å−9700 Å) plus 3 standard broad-band near-infrared (NIR) filters (J, H, and K s ) over 8 different regions of the northern sky (Moles et al 2008). The survey has the aim of understanding the evolution of galaxies throughout cosmic time by sampling a large enough cosmological fraction of the universe, for which reliable spectral energy distributions (SEDs) and precise photometric redshifts (z p ) are needed.…”
Section: The Alhambra Surveymentioning
confidence: 99%
“…The simulations of Benítez et al (2009), which relates the image depth and the accuracy of the photometric redshifts to the number of filters, have demonstrated that the filter set chosen for ALHAMBRA can achieve a photometric redshift precision that is three times better than a classical 4−5 optical broad-band filter set. The final survey parameters and scientific goals, as well as the technical properties of the filter set, were described by Moles et al (2008). The survey has collected its data for the 20+3 optical-NIR filters in the 3.5 m telescope at the Calar Alto observatory, using the wide-field camera LAICA (Large Area Imager for Calar Alto) in the optical and the OMEGA2000 camera in the NIR.…”
Section: The Alhambra Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The ALHAMBRA 1 (Advanced, Large, Homogeneous Area, Medium-Band Redshift Astronomical) survey provides a photometric dataset over 20 contiguous, equal-width, nonoverlapping, medium-band optical filters (3500−9700 Å) plus 3 standard broad-band NIR filters J, H, and Ks over 8 different regions of the northern hemisphere (Moles et al 2008). The survey aims to understand the evolution of the structures and the different families of extragalactic sources throughout cosmic time by sampling a large enough cosmological fraction of the universe.…”
Section: Photometric Data: the Alhambra Surveymentioning
confidence: 99%